Sources of Weapon System Cost Growth Analysis of 35 Major Defense Acquisition Programs - Bolten, Joseph G. (RAND Corporation, 2008)
This analysis uses data from Selected Acquisition Reports to determine the causes of cost growth in 35 mature major defense acquisition programs. Four major sources of growth are identified: (1) errors in estimation and scheduling, (2) decisions by the government, (3) financial matters, and (4) miscellaneous. The analysis shows that more than two-thirds of cost growth (measured as simple averages) is caused by decisions, most of which involve quantity changes, requirements growth, and schedule changes.